PENGARUH MODEL KOOPERATIF BERBANTUAN AUDIO VISUAL PEMBELAJARAN IPS TERHADAP HASIL BELAJAR DI SEKOLAH DASAR - Anjas Rivaldi; Suhardi Marli; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThis study aims to analyze the influence of the application cooperative model assisted audio-visual media in Social Science learning on the learning outcomes of  V grade Elementary School 27 in Southeast Pontianak. The method  used is experimental with Pre-Experimental Design and non equivalent control group design. The population of all students from two classes 54 people. the sample of this study is the students of VB class which amounted to 26 people as  experimental class and the VA class learners as  control class which amounted to 28 people. Data collection techniques used are measurement techniques and data collection tools is a written test of multiple choice. Based on the data analysis, the result of  average post-test of the experimental class class is 80,04 and the mean post-test control 74,07. Hypothesis test results using t-test (Polled Variance) obtained t count = 2.993 while for degree of freedom (28+26-2=52) with significant level α = 5% obtained t table = 1.676, which means t count > t table, this proves that there is influence of applying cooperative model of audio-visual media in Social Science learning. Based on the calculation of effect size (ES) obtained ES = 0.57which includes medium criteria.  Keywords: Influence, Cooverative Model, Audio-Visual, Social Science,  Learning       Outcomes